Ruptured Large Gastrointestinal Stromal Tumor: A Case Report and Review of Literature - Javereeya Abdul Jabbar; Amr Elmekresh; Yousif Eltayeb (Case Reports in Surgery)
Gastrointestinal stromal tumors (GIST) account for the majority of non-epithelial, mesenchymal tumors occurring in the gastrointestinal tract. Usually, the tumor measures a few centimeters, and cases larger than 15 cm are rare. Here, we report a rare case of a previously healthy 50-year-old woman, with generalized abdominal pain and increased abdominal girth for over nine months. Imaging showed a very large cystic lesion (21 cm×15 cm×24 cm) arising from the greater curvature of the stomach with rupture of the lesion into the intraperitoneal space. The patient was taken for exploratory laparotomy, which revealed a ruptured large cystic mass (21 cm×15 cm×24 cm) occupying the upper abdomen and encompassing the greater curvature of the stomach, body, and tail of the pancreas, as well as part of the spleen.